2022
DOI: 10.51847/8dk1wcpfhd
|View full text |Cite
|
Sign up to set email alerts
|

Accounting Students' Perceptions on A Role of Distance Education in Their Soft Skills Development

Abstract: A paradigm shift has taken place in distance education as a new technique of learning and teaching, switching the focus to students' learning, skills, and competencies. Distance education has been the available alternative enforced as a measure to prevent the spread of the COVID-19 Pandemic in higher education. The study aims to investigate students' perception of whether the distance education environment is capable of providing students with soft skills. Therefore, this study focuses on measuring this role f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The use of e-learning systems and their digital tools in the assessment are appreciated by accounting students compared with a traditional on-campus paper assessment (Helfaya, 2019;Marriott, 2009), and their performance improves with online assessments (Aisbitt, & Sangster, 2005;Duncan et al, 2012;Haidar, 2022). There is a positive and significant relationship between the students' use of e-learning systems and their performance in the final assessments in accounting courses (Perera, & Richardson, 2010).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…The use of e-learning systems and their digital tools in the assessment are appreciated by accounting students compared with a traditional on-campus paper assessment (Helfaya, 2019;Marriott, 2009), and their performance improves with online assessments (Aisbitt, & Sangster, 2005;Duncan et al, 2012;Haidar, 2022). There is a positive and significant relationship between the students' use of e-learning systems and their performance in the final assessments in accounting courses (Perera, & Richardson, 2010).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…According to Arquero et al (2023) communication barriers have a negative relationship with group work self-efficacy, and therefore educators should develop both teamwork and communication skills in students and thus reduce communication concerns. Haidar (2022) conducted a perception analysis of soft skills and distance education and found that distance education has a positive effect on the development of soft skills. According to Kotze and Miller (2023), teamwork, relationship building, emotional intelligence and leadership or professional skepticism should be developed in schools.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Language learning is a long, complex and multifaceted process [1,2]. For a long time, language scholars, researchers and professional instructors have attempted to approach this process through different perspectives [3,4].…”
Section: Introductionmentioning
confidence: 99%